Sarcolobus cambogensis (Marsdenieae, Asclepiadoideae, Apocynaceae): A new rheophytic shrub from Cambodia - Mchone, Elizabeth; Won, Hyosig; Livshultz, Tatyana (Phytotaxa, 2015)
A new species of Apocynaceae from Cambodia, Sarcolobus cambogensis McHone & Livsh., is described and illustrated. Specimens of the new species, all from the Central Cardamom Region, Koh Kong Province, have morphological characters diagnostic of Sarcolobus (truncate stylehead apices and oblong corpuscula). Like Sarcolobus luzonensis (Warb.) P.I. Forst. and S. borneensis (van Steenis) P.I. Forst., S. cambogensis has a rheophytic, shrubby habit, unusual in both Sarcolobus and Apocynaceae. It differs from the latter two species in its broader leaves, larger corona, and wider caudicles.